Instagram Use and Young Women's Body Image and Self-Objectification In Egypt - Hussein, Sara (AUC Knowledge Fountain, 2021)
The present study investigates the effect of Instagram use on young Egyptian women’s body image and how it is related to self-objectification. The aim of this research is to understand how Instagram usage affects women’s body image and makes them dissatisfied with their bodies; besides, it also tests how the comments women receive on their Instagram accounts affect them positively or negatively, and how the more hours they spend on Instagram, the more pressure they face to acquire a better body shape. Additionally, it examines the direct relationship between feministic beliefs and body surveillance and self-objectification. Moreover, self-objectification and Cultivation theories have been applied in this study to understand the relationship between Instagram use and body image. A convenience sample was used and a total of 440 young Egyptian women aged between 18 to above 40 years old have completed an online survey that measured Instagram use and body image concerns as well as self-objectification. The findings showed that using photo-editing tools was not associated with body dissatisfaction. Additionally, a lack of significant moderation was found for the relationship between time spent on Instagram and body dissatisfaction. Finally, the results revealed that self-objectification and body surveillance tend to be higher than the feministic beliefs; this means that young women will evaluate themselves and their bodies more.